Menjelang reformasi : kumpulan rencana-rencana akhbar, 1997-1998 - Rustam A. Sani, 1944- (Kuala Lumpur : R Pub. Services, 2004)
Reform movement in Malaysian politics against Mahathir's government on dismissal of Anwar Ibrahim from his post as Deputy Prime Minister & Finance Minister in 1998; collected articles.
Keywords: Malaysia -- Politics and government; Malaysia -- Social conditions; Malaysia -- Economic conditions; Malaysia -- Civilization